Morphometry of Demodex species in dogs - Sirigireddy Sivajothi; Sudhakara Reddy, Bhavanam (Indian Journal of Veterinary Medicine, 2024)
The present study was carried out to record the mean length and width of gnathosoma, podosoma and opisthosoma of two different Demodex mites in dogs. The mean lengths gnathosoma, mean width of gnathosoma, podosoma and opisthosoma did not differ significantly (P>0.05); mean length of podosoma, opisthosoma and the total body differed significantly (P<0.05) between both types of mites of Demodex canis and Demodex cornei. The present study suggests that apart from examination of deep skin scrapings, tape impression smears may also be made a regular practice while dealing with demodicosis suspected dogs in order to detect the surface dweller like Demodex cornei